2021
DOI: 10.9734/jpri/2021/v33i35a31881
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Evaluation of Thiazolidinedione Derivative as Novel Antidiabetic Agents

Abstract: Thiazolidinedione derivative have Antihyperglycemic activity, they are agonists for the peroxisome proliferator-activated receptor (PPAR), which controls glucose synthesis, transport, and utilization via regulating the transcription of insulin-responsive genes. A number of novel insulin sensitizers are currently being researched. Several of these are derivatives of Thiazolidinedione, but others have different chemical structures. In this work, we created some new Thiazolidinedione derivative based on structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…have synthesized thiazolidinedione derivatives and synthesized compounds were evaluated for their antidiabetic activity. Pyridine containing compound 90 contains a pyridine ring which showed a reduction of blood sugar level at 229.68±4 mg/dL as compared to standard rosiglitazone 229.68±4 mg/dL and it is a good idea to consider using the compound as a lead material for the development of anti‐diabetic medications, as a molecular docking investigation revealed that it exhibits strong antihyperglycemic action [100] . Rathod H.C et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have synthesized thiazolidinedione derivatives and synthesized compounds were evaluated for their antidiabetic activity. Pyridine containing compound 90 contains a pyridine ring which showed a reduction of blood sugar level at 229.68±4 mg/dL as compared to standard rosiglitazone 229.68±4 mg/dL and it is a good idea to consider using the compound as a lead material for the development of anti‐diabetic medications, as a molecular docking investigation revealed that it exhibits strong antihyperglycemic action [100] . Rathod H.C et al.…”
Section: Discussionmentioning
confidence: 99%
“…Pyridine containing compound 90 contains a pyridine ring which showed a reduction of blood sugar level at 229.68 � 4 mg/dL as compared to standard rosiglitazone 229.68 � 4 mg/dL and it is a good idea to consider using the compound as a lead material for the development of antidiabetic medications, as a molecular docking investigation revealed that it exhibits strong antihyperglycemic action. [100] Rathod H.C et al have designed and synthesized biphenyl carbonitrile-thiazolidinedione conjugates as α-amylase inhibitors. Among which the compound 91 has shown promising αamylase activity with IC 50 : 0.12 μM and when compared to the conventional medication Acarbose, molecular docking data showed a considerable amount of agreement between compounds with significant α-amylase inhibitory activity and their docking scores.…”
Section: Pharmacological Characteristics Of Thiazolidine Analoguesmentioning
confidence: 99%
“…4 . Thiazolidin-4-one core is widely represented in compounds with diverse biological activities [ 74 76 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%